Ecology, Diversity, Conservation and Management of Ungulates - Friedrich Reimoser; Ursula Nopp-Mayr (Diversity, 2024)
Wild ungulates are important drivers of the dynamics of many terrestrial ecosystems and impact biodiversity at different system levels [...]